Symptom management and lifestyle interventions for people with fibromyalgia - Cara E. Brown; André R. Nelson (Advanced Exercise and Health Science)
Fibromyalgia is a complex condition with symptoms of hyperalgesia, chronic fatigue, anxiety and depression. Treating fibromyalgia symptoms typically requires pharmacological, psychological and lifestyle interventions to reduce the impact of the disease. Pharmacological interventions generally prescribed for fibromyalgia include anti-depressants, serotonin-reuptake inhibitors and benzodiazepines. Prescription of these drugs for fibromyalgia symptoms are determined by individual contraindications and tolerability. An emerging therapy for fibromyalgia pain is the use of cannabinoids for those not finding relief from conventional forms of pharmacotherapies. Due to the decreasing effectiveness of some pharmacotherapies following long-term use in fibromyalgia, lifestyle interventions and cognitive behavioural therapy should be prioritised, however, further research into these interventions is required. Dietary interventions are encouraged for treating common fibromyalgia pain and common comorbidities. High quality studies evidencing the effects of physical activity interventions for this cohort are limited and report poor adherence. There is a lack of resistance training intervention studies targeting strength and power development in fibromyalgia, and available research lacks detailed methodology. These areas require further investigation as physical activity is reported to be an effective analgesic, without the associated adverse effects of pharmacotherapies. Resistance training prescription management strategies, such as, participant-led regulation of training effort and velocity-based training monitoring, may be beneficial in fibromyalgia where pain and fatigue can impact exercise adherence and capacity.